Ireland’s Economic Outlook: Perspectives and Policy Challenges - Bergin, Adele; Morgenroth, Egdar; McQuinn, Kieran (ESRI, 2016)
The research uses a new macroeconomic-model, COSMO (COre Structural MOdel of the Irish Economy), developed by the ESRI to determine the potential path of the Irish economy in the medium to long term future. The report is divided into three parts: Part one presents a baseline projection for the economy. Part two uses COSMO to examine the potential impact of Brexit and the Common Consolidated Corporate Tax Base (CCCTB) on foreign direct investment in Ireland. Part three examines future levels of housing demands and the associated challenges for the banking sector.